Can school children reliably collect rural household data in developing countries? Evidence from Nepal. Issue 6 (17th August 2016) - Bunn, David; Sah, Keshav; Kattel, Prachanda; Kimweri, Innocent; Schwind, Jessica S.; Msoffe, Peter
ABSTRACT: Household surveys are an important tool for assessing the status or trends of rural households, farms, and communities, and for conducting research. Conducting surveys in rural communities in developing countries is expensive and logistically challenging. We investigated whether primary school children could efficiently collect household or farm data as part of their homework. We hypothesised that primary school students can collect accurate data and therefore it should not be different from the data collected by trained interviewers. The results indicate that primary schools may be an excellent resource for efficiently collecting information about rural households and farm families in developing countries.